Design and field test of a special Chinese herbal medicine harvester - Zheng, Zhi’an; Cui, Baocong; Gao, Weikai; Wei, Yubin; Wu, Min; Li, Aichao (International Journal of Agricultural and Biological Engineering, 2022)
A special Chinese herbal medicine (SCHM) harvester was designed to address the problems such as the highly labor-intensive process, low harvesting efficiency, and lack of suitable machinery. The designed machine was comprised of three main components, including a reciprocating cutter, a clamping chain, and a counter roller. In addition, a mechanical model of a plant stalk during harvester operation is established to analyze the parameters affecting SCHM harvesting: sprocket rotation speed, counter roller gap, and header inclination angle. Considering the operating mode of the harvester, all three parameters were taken as test factors, and the proportion of lost fruit, the proportion of broken capsules, and the length of the retained stem are the test indicators. According to the test results, the fruit lost was 1.14%, the broken fruit was 1.02%, the stalks with an acceptable length was 82.45% at a sprocket rotation speed of 110 r/min, a roller gap of 9 mm, and a header inclination angle of 5°. The research can provide an effective solution to solve the SCHM harvest problem. Further studies need to do for making this machine more automated and intelligent.Keywords: mechanization, chain, special Chinese herbal medicine, herb harvesterDOI: 10.25165/j.ijabe.20221505.7387Citation: Zheng Z A, Cui B C, Gao W K, Wei Y B, Wu M, Li A C. Design and field test of a special Chinese herbal medicine harvester. Int J Agric & Biol Eng, 2022; 15(5): 109–115.